Formal Female Entrepreneurship and the Shadow Economy - DiRienzo, Cassandra E.; Das, Jayoti (Journal of Economics and Behavioral Studies, 2021)
Although female entrepreneurship yields products, markets, and business models that might not exist otherwise and are relevant to economic growth and development as well as issues related to gender equality, the factors that drive female entrepreneurship is largely understudied. The primary objective of this study is to examine the relationship between the size of a country’s informal sector and the prevalence of female entrepreneurship in the formal economy. This relationship is empirically tested using a regression analysis that employs a cross-country data set of 70 countries. The analysis results indicate a significant inverse relationship between the size of the informal sector and the prevalence of formal sector female entrepreneurship. It is argued that a larger informal economy implies a greater number of women working in the informal sector due to discriminatory barriers to the formal economy. Both formal sector entrepreneurship and work in the informal economy can lessen the barrier to entry women face related to work-life balance by allowing greater flexibility in work hours; however, employment in the informal sector is a relatively poor substitute to formal sector employment as informal sector work does not include benefits, nor is it taxed or included in official statistics. Policy recommendations for encouraging formal female entrepreneurship are made. Promoting female entrepreneurship in the formal sector not only helps to close gender, inequality gaps, but also serves to improve tax systems, lessen distortions in national accounts and official indicators, and improve the provision of public goods.